A Dubbed Turkish Drama and their Effects of the Behavior of Algerian Women: A Survey Study of a Sample of Women – The City of Mesila is a Model - بن صالح نجاة (ALBAHITH ALALAMI, 2017)
The study aims to identify the effects of dubbed Turkish drama on the public through the application of a sample of the views of women. The study also attempts to monitor the causes and motives due to the act of observation and to identify the various effects of this act. In order to achieve these goals, the researcher relies on the descriptive approach in addition to the questionnaire and interviews to collect data. It ends with a number of results such as: The study aims to identify the effects of dubbed Turkish drama on the public through the application of a sample of the views of women. The study also attempts to monitor the causes and motives due to the act of observation and to identify the various effects of this act. In order to achieve these goals, the researcher relies on the descriptive approach in addition to the questionnaire and interviews to collect data. It ends with a number of results such as: 1- The majority of female respondents aged between 20 and over 50 years watch dubbed Turkish drama with dome difference in viewing levels among them2- The most important motives behind the follow-up of the female respondents of such series are the time motivation by 71,4% followed by the motivation of attraction by 19% while the respondents do not care about the approval of dubbed Turkish series with their motives3- The study reveals that the variable educational level of the respondents do not effect much in their adoption of some of the behaviors found in such series 68% of them see that these Turkish series do not serve Arab social relations while 29,9% do not agree with them.